Agenesis of the vermiform appendix in a South African population: A case series - Aleisha J. Singh; Ezra E. Anirudh; Lelika Lazarus (Translational Research in Anatomy)
Introduction: The vermiform appendix is a highly variable vestigial organ among different individuals. Despite the common embryological process, there are congenital abnormalities of the vermiform appendix such as duplicity and agenesis. Agenesis is a rare occurrence in which the vermiform appendix is absent; however, there is no effect on the individual. Case information: Six cases of appendicular agenesis within a select adult South African population are reported. Type III appendicular agenesis was prevalent (83.33 %). There was one case of type V appendicular agenesis. Conclusion: Knowledge of the anatomical variations of the vermiform appendix can assist the clinician during intra-abdominal surgeries. It will ensure thorough preparation as agenesis is an anomalous occurrence.